LAW PROTECTION OF CONSUMER OF FINANCIAL SERVICE INSTITUTIONS BASED ON NO. 1/POJK.07/2013 REGULATION - Prima Melati (Institut Pendidikan Indonesia, 2023)
This research is motivated by the spread of fraud via telephone and text messages which is very disturbing to consumers. This is due to personal data that has been spread due to low consumer data protection. So that it is necessary to carry out theoretical and practical studies to study and examine legal conseuences, legal protection and legal remedies that can be taken by consumers in carrying out transactions at financial service institutions made via telephone linked to Law Number 8 of 1999 concerning Consumer Protection Jo Service Authority Regulations Finance No. 1/PJK.07/2013 Concerning Consumer Protection in the Financial Services Sector. This research is an analytical descriptive research that describes efforts to protect the law for consumers of financial service institutions for violations in telephone transactions related to the law, using a normative juridical approach, namely reviewing and testing data based on secondary data, in the form of literature studies and supported by field study namely document examination and interviews. Based on the results of the research, the analysis of documents namely Law Number 8 of 1999 concerning Consumer Protection explains the law governing rights and obligations in the transaction process between consumers and business actors. Experts explain that, consumer protection, the Consumer Protection Act applies as a general law and overcomes other laws that are more specific, such as those related to the financial services sector. This consumer protection is supported by the Financial Services Authority Regulation Number: 1/PJK.07/2013 concerning Consumer Protection in the Financial Services Sector. The expert said that violations of consumer protection in telephone transactions can result in dispute resolution through authorized institutions or through general courts. Consumers can complain about violations in the financial services sector and can be submitted to the Directorate of Consumer Services DPKS to be resolved through a facilitation process.